Inside Cover Image, Volume 42, Issue 5. Issue 5 (24th October 2018) - Hu, Yuying; Wang, Guanghong; Pan, Siyi; Wang, Lufeng
Abstract : The inside cover image, by Yuying Hu et al., is based on the Full Article Influence of ethylene and ethephon treatments on the peel color and carotenoids of Gannan Newhall navel orange during postharvest storage, DOI:10.1111/jfbc.12534 .